The Efficacy of Translanguaging in Selected South African Mathematics and Science Intermediate Phase Classrooms - Ndhlovana, Shalom Nokuthula; Charamba, Erasmos (JOLLT Journal of Languages and Language Teaching, 2023)
The 2015 TIMSS and 2021 PIRLS results show the underachievement of our learners in reading comprehension, mathematics and science. Analysts of both assessments suggest the low performance is caused, chiefly, by the misalignment between learners’ home languages and the language of instruction. Even though today’s classrooms have become more and more culturally and linguistically diverse resulting in the majority of learners entering the classroom with a home language different from the language of instruction, the teaching of such learners still follows a monolingual trajectory. This has resulted in a drop- in the number of primary school learners exhibiting basic mathematics and scientific literacy in South Africa. Through semi-systemic review, the current study sought to explore the role language plays in concept comprehension among learners as well as examining the efficacy of translanguaging in mathematics and science classrooms. Eight studies were reviewed and results suggest that proficiency in the language of instruction plays a crucial role in comprehension of scientific and mathematical concepts. The study also shows the efficacy of translanguaging in enhancing the academic performance of learners and recommends the use of translanguaging within multilingual contexts.